2015
DOI: 10.15314/tjse.81867
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an eight-week proprioception training program on agility, quickness and acceleration

Abstract: The effect of an eight-weeks proprioception training programme on agility, quicknessand acceleration in this study which aims at determining the effect of an 8-weeks proprioceptive training on agility, quickness and acceleration, 13 students studying at the school of physical education and sports, aged 23.46 ± 2.57 on average, participated as an experimental group. 13 students studying at the school of physical education and sports, aged 22.39 ± 1.56 on average, also took part in this study as a control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although individuals with congenital blindness show structural changes in the cerebral cortex to compensate for the blindness, it has been reported that this does not lead to better postural control than individuals with typical development [ 37 ]. A few of the studies in the literature found that sports and exercise improved the postural control of blind individuals [ 4 , 15 , 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although individuals with congenital blindness show structural changes in the cerebral cortex to compensate for the blindness, it has been reported that this does not lead to better postural control than individuals with typical development [ 37 ]. A few of the studies in the literature found that sports and exercise improved the postural control of blind individuals [ 4 , 15 , 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons for this, differences in sports branches, age levels and test protocols used in evaluation can be cited. When the studies examining the effects of proprioceptive exercises on athletes in different sports branches are analyzed, it was determined that there were improvements in the agility values of the groups that were given proprioceptive training, which is usually called the experimental group (Ganesh, 2012;Goktepe, 2019;Moreira et al, 2017;Riva et al, 2016;Šalaj et al 2007;Taskin & Bicer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that foot sole and metatarsus measurements are an important component of physical fitness in balance ability. In a study that is examining the effect of proprioception training on acceleration, it was determined that increased proprioception sense had a positive effect on acceleration performance (Taşkın & Biçer, 2015). In another study, it has been determined that there is a positive correlation between wider and longer foot sole measurements and balance performance .…”
Section: Discussionmentioning
confidence: 99%